(untitled) (Research, Society and Development, 2024)
Introduction: Endometriosis is an estrogen-dependent inflammatory disease characterized by the presence of endometrial glands and stroma outside the uterine cavity. Estimates on the subject indicate that 70 million women worldwide are affected by the pathology, and that it has become one of the main reasons for hospitalization for gynecological causes in industrialized countries. Objective: to analyze the clinical-epidemiological characteristics of endometriosis in Brazil. Methodology: a literature review was carried out, based on scientific articles from Scielo and Pubmed, using the descriptors endometriosis, endometrioma, adenomyosis. Articles in Portuguese were included, published between 2000 and 2023. Furthermore, a descriptive cross-sectional epidemiological study was carried out based on the SUS health information department (DATA/SUS) between January 2012 and October 2023, using the variables: hospital admissions, mortality rate, deaths, age group, color/race, sex, nature of care and health macro-region, average hospital stay. Results: 66,775 hospitalizations occurred due to endometriosis and the highest number of hospitalizations was in 2022. The Southeast region was the most reported in terms of the number of hospitalized patients and individuals who died due to endometriosis. The largest age group affected was between 40 and 49 years old. Conclusion: Endometriosis is a costly disease for the public coffers and is related to early diagnosis and correct treatment for a good prognosis.